Development of Liquid-Chromatography Tandem-Mass-Spectrometry Method for Determining Environmental Contamination by Powdered Medicinal Drugs in Pharmacies. (12th November 2021) - Hasegawa, Shiori; Inaba, Ryoichi; Nakamura, Hiroki; Kato, Yamato; Nakao, Satoshi; Hirade, Kouseki; Suzuki, Takaaki; Iwata, Mari; Kato, Takeshi; Iguchi, Kazuhiro; Yamada, Masahide; Hioki, Atsushi; et al.
The environment and personnel are both exposed to powdered pharmaceuticals inside pharmacies. This makes developing new methods for rapidly determining such contaminants an important objective. In this study, we developed a liquid-chromatography tandem-mass-spectrometry (LC–MS/MS) method for the simultaneous qualitative and quantitative determination of powdered medicinal drugs, such as famotidine, risperidone, lansoprazole, olanzapine, haloperidol, clarithromycin, promethazine, levomepromazine, and chlorpromazine. The method involves the use of acetaminophen as the internal standard, an LC–MS/MS method with a core–shell column, and a 10 mM ammonium formate/acetonitrile gradient mobile phase. The analytes were separated within 14 min, and MS with an electrospray ionization source in positive-ion mode was used. The limits of detection for the 9 drugs were .1-8.4 ng/mL. Linear calibration curves in the 10-50 000 ng/mL range were constructed, and inter-day accuracies of 92.6-113.8% were determined for the 9 drugs. The coefficients of variation were less than 14.6%. These data suggest that the proposed method is applicable for the routine assaying of powdered-medicine contamination in pharmacies.